HUBUNGAN ANTARA METODE BERMAIN LEMPAR BOLA DAN PENINGKATAN KETERAMPILAN PASSING BAWAH BOLA VOLI SERTA ADAPTASI BIOLOGIS PADA SISWA KELAS IV SDN NAPUNGLANGIR - Novenrius Sini Timba, Frederiksen (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine the effect of using the ball throwing method in improving volleyball passing skills in class VI students at Napunglangir Elementary School. This research uses quantitative research to examine the effect of using the ball throwing method in improving volleyball underpassing skills in class VI students at Napunglangir Elementary School. The population of this study was class VI students at SDN Napunglangir for the 2024 academic year with a total of 27 students consisting of 11 boys and 16 girls. Data collected using multiple choice questions. The data collected was analyzed using the SPSS 16 application. Based on the results of the research and discussion, it can be concluded that there is an influence of using the throwing ball playing method in improving volleyball underpassing skills in class VI students at Napunglangir Elementary School. This result is proven by the data which shows that the average pretest score is 65,00 while the average posttest score is 73.89. By using the t-test, the t count was 3.951 and the t table value was 2.056.